Pengaruh Diskon dan Flash Sale Terhadap Impulsivitas Konsumen pada Marketplace Tiktok Shop - Dwi Juni Juniar; Ismunandar; Muhajirin (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of discounts and flash sales on consumer impulsivity in the TikTok Shop marketplace, focusing on Generation Z consumers in Bima City. This research employed a quantitative approach using a survey method. The sample consisted of 90 respondents selected through purposive sampling, with criteria including Generation Z consumers residing in Bima City, owning a TikTok Shop account, and having made purchases during flash sale programs. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial (t) tests, simultaneous (F) tests, and the coefficient of determination. The results indicate that discounts have a positive and significant effect on consumer impulsivity, whereas flash sales do not have a significant effect on consumer impulsivity. Simultaneously, discounts and flash sales have a positive and significant effect on consumer impulsivity in the TikTok Shop marketplace. These findings suggest that discount programs are a more dominant factor in encouraging impulse buying behavior among Generation Z consumers. This study is limited to Generation Z consumers in Bima City; therefore, future research is recommended to expand the study area and incorporate additional variables that may influence consumer impulsivity